99 A regional simulated patient programme to promote excellence in simulation-based education. (17th November 2016) - Greene, L; Hellaby, M; Webster-Henderson, B; Tuttle, N; Nestel, D; Gough, S
Abstract : The term 'Simulated Patient' (SP) commonly refers to people trained to portray the role of a patient, relative, carer or co-worker in healthcare education. 1 This project aimed to develop, pilot and evaluate a bespoke, evidence-based training programme for Trainers and SPs in the North West of England. The regional SP Programme incorporates the 'SP Train-The-Trainer' (SP3T) and 'Train-The-SP' (2TSP) e-learning and workshops. A pragmatic, mixed-methods design facilitated a comprehensive exploration of the SP Programme. University ethical approval was obtained. Data collection methods included: A regional survey (n = 89 from 24 different organisations) Electronic evaluation questionnaire featuring open and closed questions; SP3T (n = 18) and 2TSP (n = 34) SP3T participant focus groups (n = 18) to explore course delivery methods and resources Usability testing of the SP Database and SP Passport in healthcare organisations (n = 5). The survey identified variances in SP terminology, recruitment, payment, contracts, risk assessment, training and quality assurance procedures. Survey findings were used to develop the SP Common Framework and SP3T package. 2 The SP3T package 2 was positively reviewed by all pilot participants (SP trainers). The depth of information and content was considered appropriate for novice and experienced simulation facilitators. The 2TSP package 3 was found to be stimulating, useful, flexible, and provided a good level of activity. SP Database testing confirmed usability in organisations with diverse IT infrastructures. The SP Passport was valued to track, record and monitor SP training and involvement. The SP Programme is now implemented throughout the region. The SP Common Framework and SP Programme are designed to empower simulation trainers to effectively work with SPs in education and training, thus promoting educational excellence. It is envisaged that engagement with well-trained SPs will improve education for the health and social care workforce and ultimately lead to improvements in patient safety and public engagement. References: Nestel D, Bearman M. Chapter 1: Introduction to simulated patient methodology. In: Nestel D, Bearman M, eds. Simulated patient methodology: theory, evidence and practice. West Sussex: Wiley Blackwell, 2015:1 –4. Gough S, Greene L, Nestel D, Hellaby M, MacKinnon R, Natali A, Roberts S, Tuttle N, Webster B. Simulated patients: a standardised, quality assured approach to training and implementation. Final Project Report. Manchester: Health Education North West, 2015. Greene L, Gough S. Simulated Patients: blending performing arts pedagogy and healthcare education. Final Project Report. Manchester: Health Education North West, 2015.